Napoléon et la Guerre d’Espagne à travers les manuels de français pour Espagnols du XIXe siècle et début du XXe - Denise Fischer Hubert (Carnets)
This paper intends to study the consequences that the invasion carried out by Napoleon had on the French studies and what image of Napoleon appeared in the textbooks throughout the 19th century and at the beginning of the 20th. Sometimes they are simple reflections made by the author that illustrates a grammatical rule, in this case it is about loose sentences. Sometimes it is about texts selected from French authors, meant for reading and translation, which glorifies the figure of the emperor or, on the contrary, belittles it; the choice of these readings depends on the nationality and the personal opinions of the author of the textbook. We can also find short stories and epistolary interchanges. We point out that the perception and the interpretation of the Napoleonic gesture developed during the century: few references immediately after the War of Independence, frequent from the middle of the 19th century, but disappearing after 1950.